Peran Pelatihan SDM dalam Mendukung SDGs 2030 pada Pelaku UMKM - Khusnul Heikal Irsyad; Denny Murdani (MAN 4 Kota Pekanbaru, 2026)
Sustainable Development Goals 2030 is an achievement that is aspired by all countries through the United Nations as an effort to create a healthy environment, the form of Indonesia's involvement in implementing the Sustainable Development Goals 2030 has been planned based on Presidential Decree no. 59 of 2019. In the business world there are business actors and management where there is a training used by each business actor to form a workforce. This study aims to determine the implementation of environmentally friendly training in business actors, as well as to provide an overview if business actors through training their workforce are involved in realizing the Sustainable Development Goals 2030 with a focus on the goal of Sustainable Development number 4 with point 4.4, namely quality education where indicators regarding education itself are one of the indicators in training, in this case providing knowledge about healthy environmental management from a small and medium perspective. The method in this study uses a qualitative methodology where the data obtained are the results of semi-structured interviews and the analysis used is verbatim with a sampling technique that is purposing sampling on business actors and families. Through this research, the researcher tries to contribute to sustainable development and it is hoped that this research can be used as a consideration for the establishment of a Sustainable Development Goals Center at the university.